Intellectual movements and their impact on Islamic ruleIn Andalusia during the fourth century AH / tenth century AD (Journal of the College of Basic Education, 2025)
Many intellectual movements appeared in Andalusia during the fourth century AH. They had an impact on the successive political developments that Andalusia witnessed with the beginning of the era of sects in light of the climate of intellectual and cultural freedom, which made every prince employ a group of scholars and thinkers to support his system of rule. It can be said that the intellectual movements in Andalusia during this period had a major impact on Islamic rule in the region, and played a pivotal role in its formation. It also contributed to strengthening and developing religious, philosophical and scientific thought, which led to a broad scientific and cultural renaissance. The ideas and principles adopted by these movements influenced the policies of the rulers, which pushed them towards adopting more open policies. The study of this topic goes back to the importance of the time period that witnessed political and cultural developments, and intellectual movements had an impact on governance and politics in Andalusia, as well as cultural diversity in Andalusia. Which gives the study of the subject richness and diversity, and the importance of the subject lies in understanding the development of Islamic rule in Andalusia and explaining how intellectual movements influenced the political and cultural aspects. The study aims to analyze intellectual movements, identify prominent intellectual figures during the fourth century, and demonstrate their influence on governance and politics.